2016
DOI: 10.1021/acs.est.6b03280
|View full text |Cite
|
Sign up to set email alerts
|

Gas Phase Thermal Oxidation of Endosulfan and Formation of Polychlorinated Dibenzo-p-dioxins and Dibenzofurans

Abstract: This paper investigates the thermal decomposition of technical endosulfan under oxidative conditions and the subsequent formation of polychlorinated dibenzo-p-dioxins, polychlorinated dibenzofurans (PCDD/F, dioxins), and their precursors. Both quantum chemical calculations and laboratory experiments were employed to investigate the pathways of oxidation of endosulfan. The laboratory scale apparatus used consists of a tubular reactor and product collection system and analysis train. The results report the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…From our present studies of oxidation of HCCP in both an unpassified reactor (where the influences of O 2 ( 1 Δ g ) are implicated) and a passified silica reactor, we have found that maximum rates of decomposition of HCCP and formation of Cl and of HCB occur at O 2 concentrations in the N 2 bath gas of between 6 and 10%. In our earlier study of oxidation of endosulfan, the same range of O 2 concentrations was found to produce the highest yields of PCDD/F . We now attribute this maximum in PCDD/F yields in endosulfan and other cyclodienes to conditions that maximize the rate of decomposition of hexachlorocyclopentadiene.…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations
“…From our present studies of oxidation of HCCP in both an unpassified reactor (where the influences of O 2 ( 1 Δ g ) are implicated) and a passified silica reactor, we have found that maximum rates of decomposition of HCCP and formation of Cl and of HCB occur at O 2 concentrations in the N 2 bath gas of between 6 and 10%. In our earlier study of oxidation of endosulfan, the same range of O 2 concentrations was found to produce the highest yields of PCDD/F . We now attribute this maximum in PCDD/F yields in endosulfan and other cyclodienes to conditions that maximize the rate of decomposition of hexachlorocyclopentadiene.…”
Section: Resultsmentioning
confidence: 51%
“…To eliminate the surface effect, we coated the silica reactor with boron oxide (see details in the Supporting Information) as satisfactory boron oxide coating appears transparent. The flow reactor, product collection system, and analysis train have been described in detail in our earlier publications , and associated Supporting Information. A syringe pump was used to introduce reactants into the system and dilute with carrier gas.…”
Section: Experimental Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…In gases released during thermal decomposition of endosulfan, a polychlorinated pesticide, Dharmarathne et al [11] identified chlorinated styrenes and chlorinated benzenes, major precursors of toxic polychlorinated dibenzodioxins and dibenzofurans (PCDD/F). Moreover, during oxidative studies on that pesticide, they observed large concentrations of PCDD/F [18]. Thermal decomposition of permethrin can also be a potential source of PCDD/PCDF [12].…”
Section: Introductionmentioning
confidence: 99%